Using Visual Scaffolding Strategy for Teaching Reading in Junior High School - Lestari, Nurul Fauziyah; Misdi, Misdi (Universitas Swadaya Gunung Jati, 2016)
This research was aimed to investigate the effectiveness of using visualscaffolding strategy in teaching reading comprehension at the eighth grade of juniorhigh school. The design of this study was a quasi experimental study. The subjectswere the students of state junior high schools in Cirebon, Indonesia. The data wereobtained by administering reading test and from observation as a supporting dataanalysis. The data of the test were analyzed by using t-test formula to know thedifference of the students’ comprehension in reading narrative text between twogroups. Meanwhile the result of the observation was analyzed descriptively. Theresults indicate that there was a significant difference on students’ learning resultbefore and after Visual Scaffolding applied.